2020
DOI: 10.1109/access.2020.3035829
|View full text |Cite
|
Sign up to set email alerts
|

Requirements Change Management Challenges of Global Software Development: An Empirical Investigation

Abstract: The software organizations rapidly adopting global software development (GSD) to gain the economic and strategic benefits. Besides, GSD faces many challenges that mainly concerned with the requirements change management (RCM). This study aims to identify and empirically validate the factors that can negatively influence the RCM process in GSD. To this end, literature review and questionnaire survey were conducted for the investigation and validation of RCM challenges. A total of 31 RCM challenges were identifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 46 publications
0
28
0
Order By: Relevance
“…The primary studies were selected from a limited number of digital repositories for the derivation of factors that might cause some relevant publications to be missing. But it is not a systematic problem as discussed by previous studies [49], [65], [66]. There is also a probability that the data extracted would be unreliable and contain certain inconsistencies.…”
Section: Study Limitationmentioning
confidence: 85%
See 3 more Smart Citations
“…The primary studies were selected from a limited number of digital repositories for the derivation of factors that might cause some relevant publications to be missing. But it is not a systematic problem as discussed by previous studies [49], [65], [66]. There is also a probability that the data extracted would be unreliable and contain certain inconsistencies.…”
Section: Study Limitationmentioning
confidence: 85%
“…The aim of the pilot test is to review the survey instructions for readability, to check the understandability of the included factors in order to overcome uncertainty, and to estimate the time taken to complete the questionnaire. Furthermore, the previous studies [10], [11], [15], [49] have shown that pilot testing with experts guarantees that the questionnaire is reliable, precise, and easy to understand.…”
Section: ) Questionnaire Pilot Testingmentioning
confidence: 99%
See 2 more Smart Citations
“…The literature indicates BA8 (Lack of familiarity with tools and techniques) as a critical challenge for RE process in the GSD environment. Akbar et al [60] and Khan et al [11] pointed out that requirement elicitation methods are required as RE partitioners are less aware of tools and scheduling activities. The main practices of requirement elicitation are interviews, questionnaires, workshops and user observations that will help practitioners to gather information about certain tools and techniques, which will help them to maintain workflow in the GSD environment.…”
mentioning
confidence: 99%